In vitro metabolism of carotenoids, ÃŸ carotene and lutein into retinoids in amphibians - Baruah, Pinky; Goswami, U C (Journal of Ecobiotechnology, 2012)
Carotenoids are a family of over 600 natural lipid-soluble pigments that are produced within microalgae, phytoplankton, and higher plants. Of these only 50 have provitamin A activity, with the capacity to be transformed into retinol and dehydroretinol. Animals are unable to synthesise carotenoids de novo. As animals lack the ability to synthesize vitamin A, they are dependent on dietary intake to provide adequate levels of vitamin A. Vitamin A (retinol) and its naturally occurring and synthetic derivatives are collectively referred to as retinoids. Retinoids are important metabolites of carotenoids that have at least one non-hydroxylated ring system of the β-type, e.g. carotenes (β-carotene, α-carotene, and γ-carotene) and xanthophyls (β-cryptoxanthin and echinenone). The pigmentation and colouration in amphibian occur owing to the deposition of carotenoids from their metabolism by consuming the carotenoids through foods from their habitat or through conversion of these carotenoids into different metabolites during development. The status of the retinoids formed through conversion of carotenoids was examined from the lipid extracts of the carotenoid administered tadpoles of Duttaphrynus melanostictus and Haplobactrachus tigerinus. The extracts were subjected to UV –VIS spectrophotometer for tentative analysis of the retinoids formed and then by the HPLC procedures for final results. The findings show that larval forms of amphibians of both the species Duttaphrynus melanostictus and Haplobactrachus tigerinus can convert β–carotene to retinol and lutein to dehydroretinol. The conversion of carotenoids into different retinoids is explained through the mode of cleavage of the carotenoids molecules.